2005
DOI: 10.1111/j.1469-8137.2005.01592.x
|View full text |Cite
|
Sign up to set email alerts
|

Pollinator limitation and inbreeding depression in orchid species with and without nectar rewards

Abstract: Summary• Many orchids produce no nectar rewards. Foraging pollinators should visit more flowers per inflorescence in species with nectar, which could increase geitonogamous self-fertilization. If a history of selfing decreases genetic load, then nectar-producing orchids should harbour lower inbreeding depression than nectarless species.• Here, I tested this hypothesis by quantifying inbreeding depression and pollinator limitation in populations of three closely related orchid species, one of which provides nec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
53
3
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(65 citation statements)
references
References 74 publications
6
53
3
3
Order By: Relevance
“…Nectariferous orchids are generally more successful in setting fruit than are nectarless species (Neiland and Wilcock 1998;Johnson and Nilsson 1999;Smithson 2006) and our data for six terrestrial species support this trend. However, contrary to expectation, there was no evidence that the presence of nectar improved fruit set among the 17 epiphytes.…”
Section: Discussionsupporting
confidence: 86%
“…Nectariferous orchids are generally more successful in setting fruit than are nectarless species (Neiland and Wilcock 1998;Johnson and Nilsson 1999;Smithson 2006) and our data for six terrestrial species support this trend. However, contrary to expectation, there was no evidence that the presence of nectar improved fruit set among the 17 epiphytes.…”
Section: Discussionsupporting
confidence: 86%
“…Compared to parental species, previous study demonstrated that O. xbivonae showed low fruiting values in open-pollinated flowers and the absence of any form of postmating isolation (PELLEGRINO et al 2009). The low levels of reproductive success, the lack of post-zygotic barriers and of F 2 (or later) generations (PELLEGRINO et al 2009) suggest that the mycorrhizal symbiosis imposes no constraints on the survival of hybrids, and that the lack of pollinators appears to strongly limit hybrid fitness, as has previously been reported in parental species (PELLEGRINO et al 2010) and other deceptive orchids (MATTILA and KUITUNEN 2000, PELLEGRINO et al 2005, SMITHSON 2006.…”
Section: Discussionmentioning
confidence: 54%
“…Avoidance of geitonogamy, the transference of pollen between Xowers on the same individual, has received considerable attention as a possible selective factor in the evolution of deception in orchids (Dressler 1981(Dressler , 1993Ackerman 1986;Johnson and Nilsson 1999;Johnson et al 2004;Smithson 2002Smithson , 2006). The argument is that Xowers with pollen packages instead of individual pollen grains should suVer strongly from pollen and stigma discounting because self-pollination completely eliminates such Xowers' chance to export pollen and at the same the stigmas' chances to receive additional outcrossed pollen (Harder and Barrett 1995).…”
Section: Introductionmentioning
confidence: 99%